Development of education in Western Kazakhstan in the 60-80-s of the XX century - Taichikova, K. (Karaganda University named after academician E.A.Buketov, 2023)
The article discusses the main stages of education development in the region. Particular attention is devoted to the reasons for the lag in implementation rate of general secondary and vocational education. The introduction of extensive ways of development at the expense of increasing volume of the studied material, without considering the quality of teaching and the development of independent and critical thinking skills of students. The lack of teaching facilities providing the education system with highly qualified personnel. Correlation of education development pace in the region with the republican rates in general. The role of government reforms in overcoming the mentioned problems.
ХХ ғасырдың 60–80-жылдарындағы Батыс Қазақстандағы білім беру орындарының дамуы
Развитие учреждений образования в Западном Казахстане в 60–80-х годах ХХ века
Keywords: education; indicators; primary school; secondary and correspondence schools; schools for working youth; staff; general education; industrial training; vocational training facilities; reforms